(untitled) (Research, Society and Development, 2020)
Floristic surveys are the basis of phytodiversity knowledge and when carried out in protected areas add value because they can generate incentives for conservation and subsidies for management plans. With the objective to contribute to flora knowledge in Piaui State, Brazil, a floristic study was developed in the riparian forest Uruçuí-Una Ecological Station. This station has a 135.122,29 ha area and is in Baixa Grande do Ribeiro municipality, Piauí, in Northeast of Brazil. The area is in Cerrado’s phytogeographical domain, with riparian forest along the river Uruçuí-Preto, which borders part of its area. The survey was conducted from samples collected of woody vascular plants in an area of approximately 4.5 ha on the left bank of Uruçuí-Preto River. The samples collected were properly herborized, taxonomically identified, and stored in herbaria Graziela Barroso (TEPB) and Delta do Parnaíba (HDELTA). The study resulted in 90 species, 71 genus, and 37 families. Except for Tilesia baccata species, Asteraceae naturalized, all species are native to Brazil, and 21.50% are also endemic in Brazil and 6.45% endemic in Cerrado. Most species, i.e 78.49% were not evaluated for the extinction risk, while 15.05% are classified in the Little Worrying category and only, Bowdichia virgilioides is in the condition of Near Threatened. This study contributes significantly to the scientific literature as it is the second floristic survey presented for this conservation unit since 1984, and the first study carried out in the riparian forest in this protected area of the Brazilian Cerrado.